Forensic Assistance Project: Consultant Report 1999-035 Goražde II Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Drayer, Francine Between 13 July and 15 July 1999 the RS Commission for Tracing Prisoners and Missing Persons, exhumed a Minimum Number of Individuals of 37 sets of human remains from various locations in the vicinity of Goražde. 27 bodies were exhumed from the Koljevići Cemetery; two sets from a garden behind a house in the city; one set from a burned house near Pundol; two sets from the basement of a burned house and one set of surface remains from a field near Podmiera; two sets from a field near Gornja Bukavica; and two sets from Liščići. Place of Exhumation: Goražde Exhumation Site: Goražde City Site 1, Goražde City Site 2, Pundol, Koljevići Groblje (Cemetery), Podmiera, Gornja Bukavica, Liščići Date of Exhumation: 13-15 July 1999 Minimum Number of Exhumed Individuals: 037